2017
DOI: 10.1136/bcr-2017-221094
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic elbow arthrotomy after motorcycle accident not evident on CT

Abstract: An 84-year-old man sustained a motorcycle accident resulting in a left elbow laceration. Orthopaedics was consulted to rule out traumatic arthrotomy. Radiographs and CT of the left elbow showed no acute osseous abnormalities and no evidence of traumatic arthrotomy. The wound was irrigated, dressed and splinted. On follow-up, the patient reported that he had been given clindamycin on a return visit to the emergency department for increased drainage. On inspection, the patient's wound was found sutured and drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Each patient was then able to undergo minor surgical intervention of irrigation and debridement with a short course of prophylactic oral antibiotics to prevent a deep infection or septic joint. Per our literature review ( Table 1 ), most TEA detection literature references cadaveric studies [ 6 , 12 ] and only one human case report [ 3 ]. In general, the majority of traumatic arthrotomy literature pertains to the knee, which has demonstrated unparalleled results to the elbow and may cloud the judgment of TEA detection method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each patient was then able to undergo minor surgical intervention of irrigation and debridement with a short course of prophylactic oral antibiotics to prevent a deep infection or septic joint. Per our literature review ( Table 1 ), most TEA detection literature references cadaveric studies [ 6 , 12 ] and only one human case report [ 3 ]. In general, the majority of traumatic arthrotomy literature pertains to the knee, which has demonstrated unparalleled results to the elbow and may cloud the judgment of TEA detection method.…”
Section: Discussionmentioning
confidence: 99%
“…The only case report on TEAs thus far was published by Bunyasaranand et al [ 3 ]. Their patient sustained a 6 cm elbow laceration from a motorcycle accident.…”
Section: Discussionmentioning
confidence: 99%
“…SLT has been studied in the knee and ankle, with the recommended infusion volumes reported as 155 to 194 mL and 10 to 60 mL, respectively [9][10][11][12][13][14][15][16]. However, there is substantial controversy regarding the fluid volume required for elbow injection [3,4]. While some reports describe a 100% sensitivity at 20ml, others demonstrated that 95% sensitivity was only attained at 40ml of injected volume [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of concurrent elbow arthrotomy may necessitate urgent irrigation with/without necrotic tissue debridement to avoid the development of septic arthritis, a devastating complication with associated irreversible joint destruction in as little as three days [ 4 , 5 ]. Notably, such aggressive interventions would not be warranted in the absence of joint arthrotomy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Computed tomography (CT) scan demonstrating intra-articular air has also shown to be a validated tool to diagnose traumatic knee arthrotomy, 7 though there is one report of CT not adequately diagnosing traumatic elbow arthrotomy. 8 Despite the well-documented use of the saline load test in the knee, ankle, and elbow, there is insufficient characterization of the test for diagnosing traumatic wrist arthrotomy. Voit et al performed the saline load test on 50 consecutive patients with periarticular lacerations, two of which involved the wrist joint.…”
mentioning
confidence: 99%